An intelligent hybrid decision support system for the management of water resources - Kazeli, Hariklea; Christofides, Tasos; Keravnou-Papailiou, Elpida (My University, 2003)
During the last two decades the scarcity of water resources is exponentially growing worldwide. Cyprus is one of the countries in the Mediterranean where the water shortage problem is evident and very severe. This paper describes an intelligent and flexible, hybrid decision support system for the management of water resources in the regions along the South Conveyor Project, the largest water development project in Cyprus. In particular, the paper presents the integrated system and its architecture, together with detailed descriptions of the hybrid components synthesizing it. Details on the implementation and preliminary evaluation of the system are also provided
Keywords: Artificial intelligence; Pattern recognition; Decision support systems; Water--Management; Dynamics; Databases